2019
DOI: 10.1002/adsc.201900521
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox‐Catalyzed Oxydifluoroalkylation of Styrenes for Access to Difluorinated Ketones with DMSO as an Oxidant

Abstract: By taking advantage of dimethyl sulfoxide (DMSO) as an oxidant, the photoredox‐catalyzed alkene oxydifluoroalkylation for formal C(sp3)−CF2R and C(sp2)=O formation is disclosed for the first time. This difunctionalization reaction employs readily available styrenes as the substrates and bromodifluoro compounds as the difluoroalkylating reagents, which can afford the difluorinated ketones in acceptable yields with excellent regioselectivity. Experiments indicate that fac‐Ir(ppy)3‐catalyzed oxydifluoroalkylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…The photoredox-catalyzed oxydifluoroalkylation of alkenes with BrCF 2 CO 2 R using dimethyl sulfoxide (DMSO) as an oxidant was reported by Tang and coworkers (Scheme 53). 125 From the proposed mechanism we can see that AgTFA as the additive assisted the formation of CF 2 CO 2 R radical via oxidative quenching of *Ir( ppy) 3 with BrCF 2 CO 2 R. The final products were isolated via Kornblum oxidation of carbocation 100 with DMSO.…”
Section: Scheme 38mentioning
confidence: 94%
“…The photoredox-catalyzed oxydifluoroalkylation of alkenes with BrCF 2 CO 2 R using dimethyl sulfoxide (DMSO) as an oxidant was reported by Tang and coworkers (Scheme 53). 125 From the proposed mechanism we can see that AgTFA as the additive assisted the formation of CF 2 CO 2 R radical via oxidative quenching of *Ir( ppy) 3 with BrCF 2 CO 2 R. The final products were isolated via Kornblum oxidation of carbocation 100 with DMSO.…”
Section: Scheme 38mentioning
confidence: 94%
“…Later, Tang and co‐workers also reported the synthesis of α,α‐difluoro‐ γ ‐ketoacetates under base free conditions by using AgTFA as additive with similar starting materials and fac‐Ir(ppy) 3 as photocatalyst (Scheme ) . Mechanistically the reaction follows the similar path as well, wherein the role of TFA is in facilitation of the removal of bromide from ethyl 2‐bromo‐2,2‐difluoroacetate.…”
Section: Ketone Synthesis Using Iridium (Ir) Based Photocatalystsmentioning
confidence: 96%
“…In 2019, the independent works from Xia et al and Li et al showed the use of bromodifluoro esters as the radical source. 44,45 The a-Br-F 2 -ester undergoes SET with the photocatalyst's excited state and the consequent homolytic cleavage of the C-Br bond to give the difluoroalkyl radical. Notably, in the latter report, the addition of a silver salt was found necessary for the reaction to proceed.…”
Section: Alkenesmentioning
confidence: 99%